2019
DOI: 10.3897/zookeys.874.35835
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the genus Ceriantheomorphe (Cnidaria, Anthozoa, Ceriantharia) with description of a new species from the Gulf of Mexico and northwestern Atlantic

Abstract: The present study presents a revision of the genus Ceriantheomorphe Carlgren, 1931, including redescriptions of the two presently recognized species, Ceriantheomorphe ambonensis (Kwietniewski, 1898) and Ceriantheomorphe brasiliensis (Mello-Leitão, 1919), comb. nov., and a description of the new species Ceriantheomorphe adelitasp. nov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Thus, based on this, the species described by Mello-Leitão should be moved to the genus Ceriantheomorphe . Carlgren (1931) mentions that the species (with this name) as described by him in that publication may be a junior synonym of C. brasiliensis Mello-Leitão 1919 , as Lopes et al (2019) have shown. Hertwig (1882) recorded a specimen of Cerianthus americanus from the Uruguayan coast whose external shape appeared to be very similar to that of Ceriantheomorphe brasiliensis .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Thus, based on this, the species described by Mello-Leitão should be moved to the genus Ceriantheomorphe . Carlgren (1931) mentions that the species (with this name) as described by him in that publication may be a junior synonym of C. brasiliensis Mello-Leitão 1919 , as Lopes et al (2019) have shown. Hertwig (1882) recorded a specimen of Cerianthus americanus from the Uruguayan coast whose external shape appeared to be very similar to that of Ceriantheomorphe brasiliensis .…”
Section: Resultsmentioning
confidence: 96%
“… Ceriantheomorphe brasiliensis : Carlgren 1931 : 2–6; Carlgren 1940 : 6,11–12; Stampar et al 2010 : 205–209; Silveira and Morandini 2011 : 3; Rodriguez et al 2011 : 52, 54–55; Spier et al 2012 : 1–3; Stampar et al 2012 : 5–6, 9; Stampar et al 2014a : 2,5,8; Stampar et al 2014b : 344, 347, 351, 353; and Stampar et al 2015a : 3; González-Muñoz et al 2016 : 5, 9; Stampar et al 2016 : 64, 67, 68; Stampar and Morandini 2017 : 690; Lopes et al 2019 : 127–148 …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Ceriantharians are morphologically distinguishable from other anthozoans by synthetizing a type of cnida, the ptychocyst, a unique feature of the group ( Mariscal, 1974 ). Tube-dwelling anemones exhibit two ranks of external and internal tentacles, the marginal and labial tentacles respectively ( Carlgren, 1912 ), and pores may occur throughout this structure ( ØVan Beneden, 1924 ; Lopes et al, 2019 ). The organization of mesenteric filaments is also different in Ceriantharia, the trilobed shape of the filaments is uncertain; and new mesenteries emerge from the multiplication chamber ( Stampar et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%